Green Synthesis of KO Nanoparticles by Cold Plasma and Study of Their Properties for Antibacterial Applications - Mohammed Jawad Kadhim; Rana Ismael Khaleel; Karar Mahdi Talib; Raghad S. Mohammed (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
This study used the cold plasma technique to synthesize potassium oxide nanoparticles (KO NPs) from potassium chloride (KCl) with roselle extract leaves and examine their physical and biological characterization. The physical properties of KO nanoparticles were examined by Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD), X-Ray Dispersive Spectroscopy (EDS), and UV–Vis Spectroscopy. Analyses of XRD show the KO NPs with an average crystallite size of 108 nm. The EDX analysis shows that high-purity KO NPs have formed. SEM image shows the shapes of some KO NPs’ spherical with varying sizes ranging from 44.66 nm to 134 nm. According to UV–Vis spectra of KO NPs, the absorption edge of these nanoparticles exhibited a blueshift with an energy gap range (Eg) from 2.8 to 3.4 eV. The biological efficacy of KO NPs was also examined by testing their antibacterial and antifungal activity. To evaluate the toxicity of the KO NPs were tested in vitro and activated as antibacterial. Against some of the test organisms, the KO NPs demonstrated good antibacterial activity.